Energy access, embryonic urbanity, and development in Amazonian villages - Brasil Júnior, Antônio César Pinho; Mendes, Rafael Castilho Faria; Tobaldini, Manuela; Júnior, Raimundo Nonato; Saigot, Louna (Sustainability in Debate, 2025)
This paper analyzes the relationship between electrification, sustainable development, and emerging urban structures in small villages of the western Brazilian Amazon. These communities, usually with one to five thousand inhabitants, present an early stage of urban consolidation that depends on reliable infrastructure to sustain wellbeing and socio environmental resilience. Using the concept of embryonic urbanity and the Social Progress Index as analytical references, the study evaluates how electricity access influences education, health, economic activity, and community organization. A case study of Caiambé, in the municipality of Tefé - western Brazilian Amazon, investigates the transition from a diesel-based power plant to a hybrid solar and battery system. Field observations and municipal indicators show that hybridization reduces fuel consumption, increases energy security, and strengthens SDG7 objectives. The results support low carbon strategies for isolated systems and offer guidance for improving the Luz para Todos with decarbonization program.